You are on page 1of 2

# April 28 2008 小老師教學講義

np np
� f (t ) = a0 + �an cos( t ) + bn sin( t )
n =1 p p
1 p
a0 =
2p �-p
f (t )dt

1 p np 1 p
an = �
p -p
f ( t )cos(
p
t ) dt = �f (t )cos(nw0t )dt
p -p
1 p np 1 p
bn = �
p -p
f (t )sin(
p
t ) dt = �f (t )sin(nw0t )dt
p -p
p

p

eit = cos t + i sin t
einw t = cos(nw0t ) + i sin(nw0t )
0

\
e- inw t = cos(nw0t ) - i sin(nw0t )
0

1
cos(nw0t ) = (einw t + e - inw t ) 0 0

2
1 -i
sin(nw0t ) = (einw t - e - inw t ) = (einw t - e - inw t )
0 0 0 0

2i 2
1 inw t

-i

0 0 0 0

n =1 2 2

a - ibn inw t an + ibn - inw t
= a0 + �( n )e + ( )e 0
Q k = -n
0

n =1 2 2
\ n = 1 ~ �� k = -1 ~ -�
� -1
a - ibn a + ibn \ �c- ne -inw0t = �c e w ik 0t

k
2 2
-1

�c e w
� � in 0t
� f (t ) = c0 + �cn e inw0t
+ �c- ne - inw0t � n
n =1 n =1 n =-�

� -1
f (t ) = c0 + �cne inw0t
+ �c e inw0t
� n =1 n =-�
n

f (t ) = c0 + �c e
n =-�
n
inw0t

n �0

2008 傅立葉級數的複數型式.doc (2008/04/28) 小江製
f (t ) = �c e
n =-�
n
inw0t

� cn = ?
April 28 2008 小老師教學講義

� p �
�w 0 = �
p
� �
� p einw0t (eimw0t dt ) = 0, where m �-n �
��
p p �
� �f (t )e imw0t
dt = ��cn einw0t eimw0t dt -p �
-p -p
n =-� � p inw t imw t �
��
� e 0
( e 0
dt ) = 2 p , where m = - n �
1 p -p �
cn = � f (t )e- inw0t dt � �
2p - p

1 p
2p �
c0 = f (t )
-p